Harnessing Endogenous Peptide Compounds as Potential Therapeutics for Severe Influenza - West, Alison C; Harpur, Christopher M; Le Page, Mélanie A; Lam, Maggie; Hodges, Christopher; Ely, Lauren K; Gearing, Andrew J; Tate, Michelle D (The Journal of infectious diseases, 2024)
Abstract Background Excessive pulmonary inflammation and damage are characteristic features of severe influenza virus infections. LAT8881 is a synthetic 16–amino acid cyclic peptide form of a naturally occurring C-terminal fragment of human growth hormone with therapeutic efficacy against influenza. Shorter linear peptides are typically easier to manufacture and formulate for delivery than larger cyclic peptides. A 6–amino acid linear peptide fragment of LAT8881, LAT9997, was investigated as a potential influenza therapy. Methods LAT9997 was evaluated for its potential to limit disease in a preclinical mouse model of severe influenza infection. Results Intranasal treatment of mice with either LAT8881 or LAT9997 from day 1 following influenza infection significantly improved survival outcomes. Initiating LAT9997 treatment at the onset of severe disease also significantly improved disease severity. Greater disease resistance in LAT9997-treated mice correlated with reduced lung immunopathology, damage markers, vascular leak, and epithelial cell death. Treatment reduced viral loads, cytokines, and neutrophil infiltration in the airways yet maintained protective alveolar macrophages in a dose-dependent manner. Sequential trimming of N- and C-terminal amino acids from LAT9997 revealed a structure-activity relationship. Conclusions These findings provide preclinical evidence that therapeutic LAT9997 treatment limits viral burden and characteristic features of severe influenza, including hyperinflammation and lung damage. Summary Excessive pulmonary inflammation and damage are characteristic features of severe influenza virus infections. LAT9997 is a linear peptide fragment derived from human growth hormone. This study provides preclinical evidence that therapeutic LAT9997 treatment limits viral burden, hyperinflammation, and lung damage.